Graphene glasses frame and manufacturing method thereof
By using PEEK matrix and composite materials of multiple reinforcement materials, the existing far-infrared glasses frame materials have been solved, and the high strength, toughness and good far-infrared release performance of graphene glasses frames have been achieved.
Patent Information
- Application Number
- CN202411776564.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-25
AI Technical Summary
The existing far-infrared glasses frame materials have high brittleness and low far-infrared release rate, which leads to the product being easily damaged during processing, wearing and daily use, affecting durability and user experience.
A composite material composed of polyether ether ketone (PEEK) particles, graphene nanoparticles, far infrared material, silica, glass fiber, polyester resin, nanocellulose and carbon nanotubes is used to perform high-temperature melt blending and injection molding through a twin-screw extruder to form a graphene glasses frame.
It significantly improves the strength and toughness of the glasses frame, reduces brittleness, while retaining excellent far-infrared release performance, extending the service life of the product.
Smart Images

Figure CN119684774A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of eyeglass manufacturing, and in particular to a graphene eyeglass frame and a manufacturing method thereof. Background Art
[0002] In the prior art, eyeglass frames that integrate far-infrared (FIR) technology are highly favored due to their potential health benefits such as promoting blood circulation and relieving eye fatigue. However, eyeglass frames currently on the market that are made of far-infrared materials such as graphene, bamboo charcoal, and ceramics generally have problems such as high material brittleness, easily damaged structure, and insufficient far-infrared emission rate, which causes the eyeglass frames to be easily damaged during processing, wearing, and daily use, affecting the durability of the product and user experience; at the same time, they need to rely on additional heating or electronic equipment to increase the emission rate, which increases the cost and complexity of use.
[0003] As an emerging high-performance material, graphene has attracted much attention due to its excellent electrical conductivity, thermal conductivity and mechanical strength, but its brittleness problem is particularly prominent. Traditional methods often fail to balance the mechanical properties and functional properties of the material, resulting in the difficulty of eyeglass frame products to meet market demand. Therefore, the present invention provides a graphene eyeglass frame and a manufacturing method thereof to solve the problems of high brittleness and low far-infrared emission rate of existing far-infrared eyeglass frame materials. Summary of the invention
[0004] In view of the deficiencies in the prior art, an object of the present invention is to provide a graphene eyeglass frame and a method for manufacturing the same.
[0005] A graphene eyeglass frame consists of the following components, measured by mass: 60-70 parts of polyetheretherketone (PEEK) particles, 10-20 parts of graphene nanoparticles, 5-10 parts of far-infrared materials, 5-10 parts of silicon dioxide, 8-12 parts of glass fibers, 4-6 parts of polyester resin, 1-3 parts of nanocellulose, and 0.5-1.5 parts of carbon nanotubes; the far-infrared material comprises one or a combination of bamboo charcoal powder and ceramic particles.
[0006] Furthermore, the combination ratio of the bamboo charcoal powder and the ceramic particles is 1:1.
[0007] Furthermore, the graphene eyeglass frame is composed of the following components by mass: 65 parts of polyetheretherketone particles, 15 parts of graphene nanoparticles, 7 parts of far-infrared materials, and 8 parts of silicon dioxide.
[0008] Furthermore, the silicon dioxide is treated with a silane coupling agent.
[0009] Polyetheretherketone (PEEK) is a high-performance thermoplastic with excellent mechanical properties and toughness. The etherketone bonds in its molecular chain structure enable the material to better disperse and absorb energy when subjected to external forces, thereby slowing down the expansion of cracks and improving the material's resistance to brittleness. PEEK's high heat resistance allows the eyeglass frames to maintain stable performance even in high temperature environments, making them less likely to deform or be damaged, further reducing the risk of brittle fracture caused by temperature changes.
[0010] Graphene nanoparticles have extremely high strength and modulus, and can form an effective reinforcement phase in the PEEK matrix. When subjected to external force, the graphene nanoparticles can bear part of the load and disperse stress concentration, thereby significantly improving the strength and toughness of the eyeglass frame; a strong interface bonding force may be formed between the graphene nanoparticles and the PEEK matrix, which helps to transfer external force to the matrix material more effectively and avoid stress concentration and crack propagation at the interface.
[0011] As a hard filler, silica can significantly improve the hardness and wear resistance of the PEEK matrix. The increase in hardness helps reduce the risk of material failure due to wear. The uniform distribution of silica particles in the PEEK matrix can form stress concentration points. When subjected to external forces, these points can disperse stress and slow down the propagation rate of cracks, thereby improving the material's resistance to brittleness to a certain extent.
[0012] Nanocellulose is a natural nanofiber with a high aspect ratio. It can act as a bridging agent in composite materials and effectively transfer stress through its long fiber structure, thereby enhancing the toughness of the material. In addition, nanocellulose has good dispersibility and can be evenly distributed in the matrix material to avoid agglomeration.
[0013] Carbon nanotubes (CNTs) have high strength and elastic modulus and can significantly improve the mechanical properties of composite materials. When CNTs are added to the matrix material, they can act as stress dispersion centers and effectively prevent the expansion of cracks, thereby improving the toughness of the material.
[0014] As a reinforcing material, glass fiber has excellent mechanical properties and good thermal stability. It can form a three-dimensional network structure in the composite material to improve the tensile strength and rigidity of the material.
[0015] As a kind of adhesive, polyester resin can improve the interfacial bonding strength of composite materials, making the bonding between the matrix material and the reinforcing material stronger. In addition, polyester resin can also improve the toughness of the material, making it less likely to break when subjected to external forces.
[0016] A method for manufacturing a graphene eyeglass frame comprises the following steps:
[0017] (1) Raw material mixing: polyetheretherketone particles, graphene nanoparticles, far-infrared material, silicon dioxide, glass fiber, polyester resin, nanocellulose, and carbon nanotubes are accurately weighed and uniformly mixed according to proportion;
[0018] (2) Melt blending: Place the mixed materials in a twin-screw extruder and melt blend them at a high temperature of 360-380°C for 5-10 minutes to ensure that all components are fully blended;
[0019] (3) Cooling and granulation after extrusion: The molten mixture is extruded into a rod through a die, then rapidly cooled, and the cooled rod-shaped material is cut into 2-4 mm long pellets for subsequent injection molding process;
[0020] (4) Injection molding: The prepared particles are fed into an injection molding machine mold, and the injection temperature is set to 360-400°C, the injection pressure is set to 60-80 MPa, and the mold temperature is set to 80-120°C for injection molding. Under high temperature and high pressure, the molten particles fill the mold cavity to form the shape of the eyeglass frame, and then cool and solidify to obtain a graphene eyeglass frame;
[0021] (5) Post-processing: The formed eyeglass frame is removed from the mold and subjected to necessary trimming and surface treatment to obtain the final product.
[0022] Furthermore, in the raw material mixing step, the mixing process adopts ultrasonic dispersion or mechanical stirring dispersion.
[0023] Furthermore, in the post-extrusion cooling and granulation step, the rapid cooling process is carried out under flowing water cooling or forced air cooling conditions.
[0024] Furthermore, the water flow velocity of the flowing water cooling is 0.5-1.5 m / s, the water temperature is 20-25°C, the wind speed of the forced air cooling is 5-10 m / s, and the air cooling temperature is 20-25°C.
[0025] Furthermore, during the melt blending and injection molding steps, the ambient humidity is lower than 5% relative humidity and the ambient temperature is 20-25°C.
[0026] Furthermore, in the post-processing step, the surface treatment process includes at least one of sandblasting, polishing, electroplating or spraying.
[0027] Far-infrared materials indirectly improve toughness by improving the microstructure and thermal properties of the material. Far-infrared radiation promotes the movement of molecular chains in the PEEK matrix, helps eliminate internal stress, and reduces the possibility of crack formation. At the same time, the addition of bamboo charcoal powder and ceramic particles also reduces defects and voids inside the material through the filling effect, improving the density and strength of the material. Silica particles treated with silane coupling agents have good dispersibility and interfacial bonding in the PEEK matrix. The hardness of silica is high, which can significantly improve the wear resistance of the eyeglass frame. At the same time, its uniform distribution also helps to disperse stress and reduce the risk of brittle fracture caused by stress concentration.
[0028] At high temperatures, PEEK particles soften and melt, and are fully mixed with graphene nanoparticles, far-infrared materials, and silica particles. During this process, the interfacial interactions between the components are gradually enhanced to form a uniform composite material system. The rapid cooling process helps to fix the morphology of the molten mixture and prevent unnecessary thermal deformation or degradation at high temperatures. Flowing water cooling or forced air cooling can quickly take away the heat and quickly solidify the material. Under high temperature and high pressure, the molten particles fill the mold cavity and form the shape of the eyeglass frame. The selection of injection molding temperature and pressure needs to ensure that the material flows fully and fills every corner of the mold while avoiding defects such as bubbles or shrinkage holes; the physical changes in the injection molding process include stages such as material flow, filling, pressure holding, and cooling and solidification, which together determine the shape and quality of the final product.
[0029] The beneficial effects achieved by the present invention are as follows: 1. The present invention optimizes the formula and manufacturing process of the composite material, combines the excellent performance of the PEEK matrix material, the wear resistance and stress dispersion effect of silica, and adds a variety of reinforcing materials such as glass fiber, nanocellulose and carbon nanotubes to reduce the generation and development of cracks, thereby jointly improving the strength and toughness of the eyeglass frame, while retaining its excellent far-infrared release performance, and significantly reducing the brittleness of the graphene eyeglass frame.
[0030] 2. The present invention utilizes the excellent mechanical properties and chemical resistance of PEEK itself, while graphene nanoparticles and glass fibers further enhance the rigidity and impact resistance of the material, and nanocellulose helps to improve the flexibility and crack resistance of the material, thereby effectively reducing brittleness.
[0031] 3. The present invention uses a silane coupling agent to perform surface treatment on silicon dioxide, thereby enhancing the interfacial bonding between silicon dioxide and other components, improving the overall stability and toughness of the composite material, and helping to reduce defects and stress concentration points inside the material, thereby reducing the risk of brittle fracture.
[0032] 4. The present invention performs high-temperature melt blending in a twin-screw extruder to ensure full fusion and uniform distribution of the components at the molecular level, improve the density and uniformity of the material, and also help eliminate residual stress and defects inside the material, further reducing brittleness.
[0033] 5. The specific mixing, melting, cooling and injection molding processes adopted in the present invention ensure the uniformity and stability of the composite material during the processing, which not only improves production efficiency, but also increases the yield of products and reduces production costs. At the same time, it also ensures the accuracy and consistency of the eyeglass frame during the manufacturing process, ensuring the excellent quality of the final product. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 A schematic flow chart of a method for manufacturing a graphene eyeglass frame used in an embodiment of the present invention;
[0035] Figure 2 The raw material formula of the graphene eyeglass frame used in the embodiment of the present invention;
[0036] Figure 3 The impact test, bending test, and fracture toughness test results of the graphene eyeglass frame used in the embodiments of the present invention;
[0037] Figure 4 These are the hardness test and fatigue test results of the graphene eyeglass frame used in the embodiments of the present invention. DETAILED DESCRIPTION
[0038] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0039] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are for describing specific embodiments rather than for limiting the scope of protection of the present invention.
[0040] When the embodiment gives a numerical range, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs.
[0041] The raw materials and equipment used in the following examples, unless otherwise specified, are common commercially available products.
[0042] The following examples use KH-550 (γ-aminopropyltriethoxysilane) silane coupling agent to treat silica, and the specific steps are: ① Add the silane coupling agent to ethanol, stir evenly, and prepare a solution with a concentration of 5%; ② Add silica particles to the silane coupling agent solution to ensure that the particles are fully immersed in the solution, and react at 50° C. for 5 hours to allow the silane coupling agent to chemically react with the hydroxyl groups on the surface of the silica particles; ③ Separate the treated silica particles from the solution and dry them at 70° C.
[0043] Embodiment 1: A graphene eyeglass frame, such as Figure 2 As shown, it is composed of the following ingredients, by mass: 65 parts of polyetheretherketone (PEEK) particles, 15 parts of graphene nanoparticles, 7 parts of far-infrared materials, 8 parts of silicon dioxide (treated with silane coupling agent), 10 parts of glass fiber, 5 parts of polyester resin, 2 parts of nanocellulose, and 1 part of carbon nanotubes; the far-infrared material is a mixture of bamboo charcoal powder and ceramic particles in a ratio of 1:1.
[0044] A method for manufacturing a graphene eyeglass frame, such as Figure 1 As shown, the following steps are included:
[0045] (1) Raw material mixing: using ultrasonic dispersion technology, polyetheretherketone particles, graphene nanoparticles, far-infrared materials, silicon dioxide, glass fiber, polyester resin, nanocellulose, and carbon nanotubes are accurately weighed and mixed uniformly according to proportion;
[0046] (2) Melt blending: The mixed materials were placed in a twin-screw extruder and melt blended at a high temperature of 370°C for 8 minutes to ensure that all components were fully blended;
[0047] (3) Cooling and granulation after extrusion: The molten mixture was extruded into a rod through a die, and then rapidly cooled under running water cooling conditions (water flow rate 1 m / s, water temperature 22°C), and the cooled rod-shaped material was cut into 3 mm long pellets;
[0048] (4) Injection molding: The prepared particles are fed into an injection molding machine mold, and the injection temperature is set to 380°C, the injection pressure is set to 70 MPa, and the mold temperature is set to 100°C for injection molding. Under high temperature and high pressure, the molten particles fill the mold cavity to form the shape of the eyeglass frame, and then cool and solidify to obtain a graphene eyeglass frame;
[0049] (5) Post-processing: The formed eyeglass frame is removed from the mold, sandblasted and polished to obtain a smooth surface to obtain the final product.
[0050] Embodiment 2: A graphene eyeglass frame, such as Figure 2As shown, it is composed of the following ingredients, by mass: 60 parts of polyetheretherketone (PEEK) particles, 20 parts of graphene nanoparticles, 7 parts of far-infrared materials, 8 parts of silicon dioxide (not treated with silane coupling agent), 8 parts of glass fiber, 4 parts of polyester resin, 1 part of nanocellulose, and 0.5 parts of carbon nanotubes; the far-infrared material is a mixture of bamboo charcoal powder and ceramic particles in a ratio of 1:1.
[0051] A method for manufacturing a graphene eyeglass frame, such as Figure 1 As shown, the following steps are included:
[0052] (1) Raw material mixing: polyetheretherketone particles, graphene nanoparticles, far-infrared materials, silicon dioxide, glass fibers, polyester resin, nanocellulose, and carbon nanotubes are accurately weighed and uniformly mixed by mechanical stirring and dispersion;
[0053] (2) Melt blending: The mixed materials were placed in a twin-screw extruder and melt blended at a high temperature of 375°C for 10 minutes to ensure that all components were fully blended;
[0054] (3) Cooling and granulation after extrusion: The molten mixture was extruded into a rod through a die, and then rapidly cooled under running water cooling conditions (water flow rate 1 m / s, water temperature 22°C), and the cooled rod-shaped material was cut into 3 mm long pellets;
[0055] (4) Injection molding: The prepared particles are fed into an injection molding machine mold, and the injection temperature is set to 390°C, the injection pressure is set to 70 MPa, and the mold temperature is set to 100°C for injection molding. Under high temperature and high pressure, the molten particles fill the mold cavity to form the shape of the eyeglass frame, and then cool and solidify to obtain a graphene eyeglass frame;
[0056] (5) Post-processing: The formed eyeglass frame is removed from the mold, polished and electroplated to improve the surface gloss and corrosion resistance to obtain the final product.
[0057] Embodiment 3: A graphene eyeglass frame, such as Figure 2 As shown, it is composed of the following ingredients, by mass: 65 parts of polyetheretherketone (PEEK) particles, 15 parts of graphene nanoparticles, 10 parts of far-infrared materials, 5 parts of silicon dioxide (treated with silane coupling agent), 12 parts of glass fiber, 6 parts of polyester resin, 3 parts of nanocellulose, and 1.5 parts of carbon nanotubes; the far-infrared material only uses bamboo charcoal powder.
[0058] A method for manufacturing a graphene eyeglass frame, such as Figure 1 As shown, the following steps are included:
[0059] (1) Raw material mixing: using ultrasonic dispersion, polyetheretherketone particles, graphene nanoparticles, far-infrared materials, silicon dioxide, glass fiber, polyester resin, nanocellulose, and carbon nanotubes are accurately weighed and uniformly mixed according to proportion;
[0060] (2) Melt blending: The mixed materials were placed in a twin-screw extruder and melt blended at a high temperature of 365°C for 7 minutes to ensure that all components were fully blended;
[0061] (3) Cooling and granulation after extrusion: The molten mixture was extruded into a rod through a die, and then rapidly cooled under forced air cooling conditions (wind speed 7 m / s, air cooling temperature 23°C), and the cooled rod-shaped material was cut into 2 mm long pellets;
[0062] (4) Injection molding: The prepared particles are fed into an injection molding machine mold, and the injection temperature is set to 360°C, the injection pressure is set to 65 MPa, and the mold temperature is set to 90°C for injection molding. Under high temperature and high pressure, the molten particles fill the mold cavity to form the shape of the eyeglass frame, and then cool and solidify to obtain a graphene eyeglass frame;
[0063] (5) Post-processing: The formed eyeglass frame is removed from the mold and sprayed with a layer of transparent wear-resistant coating to protect the eyeglass frame and increase its aesthetics, thereby obtaining the final product.
[0064] Comparative Example: A conventional PA12 eyeglass frame, composed of 100 parts by mass of polyamide 12 (PA12) particles.
[0065] A method for manufacturing a conventional PA12 eyeglass frame comprises the following steps:
[0066] (1) Screening PA12 particles to remove impurities and unqualified particles;
[0067] (2) directly placing the screened PA12 particles into a twin-screw extruder without adding any other ingredients; setting the temperature of the twin-screw extruder to 280°C, and performing melt blending extrusion for 7 minutes to ensure that the PA12 particles are completely melted and evenly mixed;
[0068] (3) Extruding the molten PA12 mixture into a rod through a die; rapidly cooling under running water cooling conditions (water flow rate 1 m / s, water temperature 20° C.); cutting the cooled rod or strip material into pellets of 3 mm in length for subsequent injection molding;
[0069] (4) feeding the prepared PA12 particles into an injection molding machine mold; setting the injection temperature to 290° C., the injection pressure to 60 MPa, and the mold temperature to 80° C.; performing injection molding, under high temperature and high pressure, the molten PA12 particles fill the mold cavity to form the shape of the eyeglass frame; then cooling and solidifying to obtain a conventional PA12 eyeglass frame;
[0070] (5) The formed eyeglass frame is removed from the mold; necessary trimming and polishing are performed to remove burrs and uneven parts; in this comparative example, in order to maintain consistency with the experimental example, no additional surface treatment is performed.
[0071] Performance test: The eyeglass frames of Example 1, Example 2, Example 3 and the comparative example were subjected to impact test, bending test, fracture toughness test, hardness test and fatigue test.
[0072] 1. Impact test: Evaluate the material's ability to resist damage when subjected to sudden impact, that is, the material's impact toughness; use a drop-weight impact tester to prepare samples according to GB / T 1843-2008 "Determination of Izod Impact Strength of Plastics" standard; fix the sample on the tester, release the impact body (drop weight) to hit the sample at a predetermined speed, and record the mass, impact speed, impact energy and impact time of the impact body; observe the damage of the sample after the impact, such as the initiation, expansion and final fracture morphology of the crack; calculate the impact toughness value based on the impact energy and sample damage.
[0073] 2. Bending test: Evaluate the material's ability to resist fracture when subjected to bending force, that is, the material's bending strength and toughness; use a three-point bending tester to prepare rectangular or circular cross-section samples according to GB / T 9341-2008 "Determination of Bending Properties of Plastics" standard, place the sample on the support of the testing machine, apply a gradually increasing bending load until the sample breaks, record the load and corresponding displacement during the loading process, observe the bending deformation process of the sample, record the load and displacement at fracture, and calculate the bending strength (maximum load divided by the cross-sectional area of the sample) based on the load-displacement curve.
[0074] 3. Fracture toughness test: Evaluate the resistance of the material to crack propagation, that is, the fracture toughness of the material; use a compact tensile testing machine to pre-create cracks or notches in the sample, ensure that the crack length, width and sample size meet the standards, install the sample on the testing machine, apply gradually increasing tensile loads until the crack propagates and causes the sample to break, record the load and crack propagation length during loading, record the load at fracture and the final length of the crack, and calculate the fracture toughness value based on fracture mechanics theory, which represents the energy required to extend a unit crack length.
[0075] 4. Hardness test: Evaluate the hardness; according to GB / T 2411-2008 "Plastic Shore Hardness Test Method", use a Rockwell hardness tester to ensure that the sample surface is flat, free of oil and oxide layer, select a suitable indenter and load, press the indenter into the sample surface and hold it for a certain period of time, then release the load and measure the depth or diameter of the indentation. The measuring tool measures the size of the indentation, and the Rockwell hardness value is calculated based on the indentation size and the load used.
[0076] 5. Fatigue test: Evaluate the durability and fatigue fracture resistance of materials under alternating stress; use a fatigue testing machine to prepare samples according to standards to ensure that the size, shape and surface quality meet the requirements. It may be necessary to pre-make notches or cracks on the samples to accelerate the fatigue process, install the samples on the testing machine, apply alternating stress (sine wave, square wave, etc.) loads, record the stress amplitude, frequency and number of cycles during the loading process, regularly observe the fatigue damage of the samples, such as the initiation and expansion of cracks, record the number of cycles when the samples break (fatigue life), and evaluate the fatigue brittleness of the materials based on the fatigue life.
[0077] from Figure 3-Figure 4 It can be seen that the impact toughness of Example 1, Example 2 and Example 3 is significantly higher than that of the comparative example (conventional PA12 eyeglass frame), which indicates that after adding graphene nanoparticles and treated silicon dioxide, the impact resistance of the material is significantly improved;
[0078] The bending strength of all examples is much higher than that of the comparative example, further proving the strengthening effect of adding graphene nanoparticles and silicon dioxide on the strength of the material. The bending strength of Example 3 is the highest, indicating that its combination of ingredients and process is the most effective.
[0079] The fracture toughness of the examples is also significantly higher than that of the comparative examples, indicating that these materials have higher resistance to crack propagation. The fracture toughness of Example 3 is the highest, which is consistent with its performance in terms of impact toughness and bending strength.
[0080] The hardness test results show that the hardness of the examples is much higher than that of the comparative examples, which is due to the addition of graphene nanoparticles and the strengthening effect of silicon dioxide after being treated with a silane coupling agent. Although the silicon dioxide in Example 2 is not treated, its hardness is still higher than that of the comparative example, but lower than that of the treated examples 1 and 3;
[0081] The fatigue life of the embodiments far exceeds that of the comparative examples, indicating that these materials have stronger durability and fatigue fracture resistance under alternating stress. The fatigue life of Example 3 is the longest, which is consistent with its comprehensive performance in impact toughness, bending strength, fracture toughness and hardness.
[0082] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A graphene eyeglass frame, characterized in that: The invention is composed of the following ingredients by mass: 60-70 parts of polyetheretherketone particles, 10-20 parts of graphene nanoparticles, 5-10 parts of far-infrared materials, 5-10 parts of silicon dioxide, 8-12 parts of glass fibers, 4-6 parts of polyester resin, 1-3 parts of nanocellulose and 0.5-1.5 parts of carbon nanotubes; the far-infrared materials include one or a combination of bamboo charcoal powder and ceramic particles.
2. A graphene eyeglass frame according to claim 1, characterized in that: The combination ratio of the bamboo charcoal powder and the ceramic particles is 1:
1.
3. The graphene eyeglass frame according to claim 1, characterized in that: The invention is composed of the following ingredients by mass: 65 parts of polyetheretherketone particles, 15 parts of graphene nanoparticles, 7 parts of far-infrared materials and 8 parts of silicon dioxide.
4. The graphene eyeglass frame according to claim 1, characterized in that: The silicon dioxide is treated with a silane coupling agent.
5. The method for manufacturing a graphene eyeglass frame according to claim 4, characterized in that: The method comprises the following steps: (1) mixing raw materials: accurately weighing polyetheretherketone particles, graphene nanoparticles, far-infrared materials, silicon dioxide, glass fibers, polyester resin, nanocellulose, and carbon nanotubes according to a certain proportion and mixing them uniformly; (2) Melt blending: Place the mixed materials in a twin-screw extruder and melt blend them at a high temperature of 360-380°C for 5-10 minutes to ensure that all components are fully blended; (3) Cooling and granulation after extrusion: The molten mixture is extruded into a rod through a die, then rapidly cooled, and the cooled rod-shaped material is cut into 2-4 mm long pellets for subsequent injection molding process; (4) Injection molding: The prepared particles are fed into an injection molding machine mold, and the injection temperature is set to 360-400°C, the injection pressure is set to 60-80 MPa, and the mold temperature is set to 80-120°C for injection molding. Under high temperature and high pressure, the molten particles fill the mold cavity to form the shape of the eyeglass frame, and then cool and solidify to obtain a graphene eyeglass frame; (5) Post-processing: The formed eyeglass frame is removed from the mold and subjected to necessary trimming and surface treatment to obtain the final product.
6. The method for manufacturing a graphene eyeglass frame according to claim 5, characterized in that: In the raw material mixing step, the mixing process adopts ultrasonic dispersion or mechanical stirring dispersion.
7. The method for manufacturing a graphene eyeglass frame according to claim 5, characterized in that: In the post-extrusion cooling and granulation step, the rapid cooling process is carried out under the conditions of flowing water cooling or forced air cooling.
8. The method for manufacturing a graphene eyeglass frame according to claim 7, characterized in that: The water flow velocity of the flowing water cooling is 0.5-1.5 m / s, and the water temperature is 20-25°C. The wind speed of the forced air cooling is 5-10 m / s, and the air cooling temperature is 20-25°C.
9. The method for manufacturing a graphene eyeglass frame according to claim 5, characterized in that: During the melt blending and injection molding steps, the ambient humidity is lower than 5% relative humidity and the ambient temperature is 20-25°C.
10. The method for manufacturing a graphene eyeglass frame according to claim 5, characterized in that: In the post-processing step, the surface treatment process includes at least one of sandblasting, polishing, electroplating or spraying.